Modelling correlations in credit portfolio risk II - Altrock, Frank; Rosenow, Bernd; Weißbach, Rafael (Technische Universität Dortmund, 2007)
The risk of a credit portfolio depends crucially on correlations between latent covariates, for instance the probability of default (PD) in different economic sectors. Often, correlations have to be estimated from relatively short time series, and the resulting estimation error hinders the detection of a signal. We suggest a general method of parameter estimation which avoids in a controlled way the underestimation of correlation risk. Empirical evidence is presented how, in the framework of the CreditRisk+ model with integrated correlations, this method leads to an increased economic capital estimate. Thus, the limits of detecting the portfolio's diversification potential are adequately reflected.
1. Band 2004 unter dem Titel "Modelling correlations in portfolio credit risk" erschienen. 2. Band 2007 unter dem Titel "Modelling correlations in credit portfolio risk II" veröffentlicht.
Keywords: Correlation; Credit portfolio; CreditRisk+ model; Latent covariates; Risk; 004